AIAA Atmospheric Flight Mechanics Conference 2010
DOI: 10.2514/6.2010-7934
|View full text |Cite
|
Sign up to set email alerts
|

Control Law Design for Perching an Agile MAV with Articulated Wings

Abstract: This paper explores the use of variable wing dihedral and variable wing twist (in conjunction with a conventional horizontal elevator) to control an aircraft performing a perching maneuver. A choice of controller architecture wherein the dihedral is employed in the forward path and the elevator and twist are employed in the feedback path, is considered. The aircraft is modeled as a multivariable linear time-varying system. A specific perching trajectory is considered; and the open-loop aircraft is longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Incidentally, the first part of the maneuver can be used for performing rapid descents in constrained space, as a substitute or complement for strategies such as the spin-based strategy discussed by Ramsey and co-authors [17]. Chakravarthy and co-authors 18 have designed a guidance algorithm based on H 2 optimal control for perching using the ideas described in this paper.…”
Section: Simulationsmentioning
confidence: 99%
“…Incidentally, the first part of the maneuver can be used for performing rapid descents in constrained space, as a substitute or complement for strategies such as the spin-based strategy discussed by Ramsey and co-authors [17]. Chakravarthy and co-authors 18 have designed a guidance algorithm based on H 2 optimal control for perching using the ideas described in this paper.…”
Section: Simulationsmentioning
confidence: 99%
“…Improvements resulting from the use of variable wing twist and movable tail boom were studied in [33] and [34]. In our prior work [5], a linear quadratic Gaussian (LQG) controller was designed to execute a perching maneuver using a combination of wing twist and wing dihedral (see Fig. 2) as control inputs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that the wing dihedral alone provides sufficient yaw control for trim, but also noted that the sign of the yaw control effectiveness changes as a function of the angle of attack and angular rates. Control laws for stabilizing and maneuvering an articulated wing aircraft have been presented in [3,8]. A roll control mechanism was demonstrated by Stanford et al [9] for an aircraft equipped with highly flexible membrane wings.…”
Section: A Literature Reviewmentioning
confidence: 99%